THE EFFECT OF PLATFORM-BASED E-LEARNING ON JUNIOR HIGH SCHOOL STUDENTS’ LEARNING OUTCOMES IN LAMPUNG PROVINCE - Mudayat Mudayat; Ahmad Syaikhu; Mualimin Mualimin; Sariyani Sariyani; Imam Syafi’i (COMPASS: Journal of Education and Counselling, 2026)
This study aims to analyze the effect of e-learning on junior high school students’ learning outcomes in Lampung Province and identify experiences and challenges in digital learning. The study employed a mixed-methods approach with a sequential explanatory design. Quantitative data were collected from 300 students using Likert-scale questionnaires and analyzed through multiple linear regression, while qualitative data were obtained through in-depth interviews with teachers and students and analyzed using thematic analysis. The research results indicate that the intensity of digital learning use and the quality of interaction have a significant impact on student learning outcomes, accounting for 62% of the variation. Qualitative findings suggest that digital learning offers flexibility in learning; however, challenges remain in the form of limited direct interaction and variations in students’ digital literacy. The integrated results indicate that the effectiveness of digital learning is determined not only by technological aspects but also by the quality of pedagogical interactions and user readiness. In conclusion, digital learning has proven effective in improving student learning outcomes, but its effectiveness is highly dependent on interaction and digital literacy factors; therefore, continuous strengthening of learning strategies and the development of digital competencies are necessary.